2018
DOI: 10.3389/fphys.2018.00348
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Derived Extracellular Vesicles Protect Against Acute Myocardial Infarction by Regulating miR-21/PDCD4 Signaling Pathway

Abstract: Acute myocardial infarction (AMI) represents a leading cause of morbidity and mortality worldwide. Extracellular vesicles (EVs) are being recognized as a promising therapeutic approach in protecting against MI. Serum is a rich source of EVs, which transports various microRNAs (miRNAs, miRs). EVs from serum have been shown beneficial for protecting against ischemia-reperfusion injury; however, their roles in AMI are unclear. In addition, whether a miRNA might be responsible for the effects of serum EVs on prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…miR-21, one of the most highly expressed miRs in mammalian cells, is modulated in cardiovascular disease (19)(20)(21)(22)(23). However, little is known regarding the expression of miR-21 in hematopoietic progenitor cells.…”
Section: Downregulation Of Mir-21 Associated With Reciprocal Changes mentioning
confidence: 99%
“…miR-21, one of the most highly expressed miRs in mammalian cells, is modulated in cardiovascular disease (19)(20)(21)(22)(23). However, little is known regarding the expression of miR-21 in hematopoietic progenitor cells.…”
Section: Downregulation Of Mir-21 Associated With Reciprocal Changes mentioning
confidence: 99%
“…For instance, mi-RNA-26a,−103, -and 107 have been shown to predominantly be regulators for insulin receptor function and free fatty acid metabolism (53,(110)(111)(112)(113)(114)(115)(116). Additionally, recent pre-clinical studies have revealed that mi-RNA-378 and mi-RNA-451 may play a crucial role in energy metabolism control through interacting with carnitine O-acetyltransferase, the peroxisome proliferator-activated receptor γ coactivator 1β, and LKB1/AMPK-signaling (117)(118)(119).…”
Section: Ev-derived Non-coding Rnas In Cardiac and Vascular Remodelinmentioning
confidence: 99%
“…Additionally, EVs accumulate in the ischemic myocardium and regulate local inflammatory responses and vascular function through Erk1/2 STAT, Akt/MAPK-NF-κB signaling pathway (69,112). Therefore, NLRP3 inflammasomes and endothelial cell-derived EVs act as cargo for a wide spectrum There is evidence showing that mi-RNA-21, after a delivery into cardiac myocytes and endothelial cells, have reduced apoptosis through decreases in Programmed Cell Death gene-4 expression, inhibition of the extracellular inhibitor of the sprout regulated kinase 1 (Spry1), and stimulation of the expression of VEGF (53,67,113). In animal models, the protective effect of microRNA-21 against ischemia-induced myocardial damage was confirmed by diminished cell apoptosis around the infarcted areas after treatment with antibody vs. miRNA-21 (114).…”
Section: Ev-derived Non-coding Rnas In Cardiac and Vascular Remodelinmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a number of studies have suggested that extracellular vesicles (EVs) from in vitro cultured-cells or serum possess cardioprotective effects due to miRNAs, already present in the EVs (34,35); however, these studies have focused on the function of EVs as protective vesicles as opposed to drug carriers. Notably, the present study, to the best of our knowledge, provides the first compelling evidence that human peripheral blood-derived exosomes may be successfully used as a delivery vehicle for miRNA.…”
Section: Discussionmentioning
confidence: 99%